Critical and Higher Order Thinking in Online Threaded Discussions in the Slovak Context - Pisutova-Gerber, Katarina; Malovicova, Jana (International Review of Research in Open and Distributed Learning, 2009)
This article describes and analyzes efforts to use collaborative asynchronous discussion forums in a three semester online education program for NGO leaders and managers in Slovakia. Slovakia, as a country with autocratic styles of teacher-centered education, presents strong barriers to the implementation of collaborative learning activities. The authors used Garrison’s four stage cognitive processing categories to analyze some of the online discussions in the program. The two higher order critical thinking categories – integration and solution – appeared in student discussions only when prompted by specific instructional techniques.